Perinatal Outcome of Twin Pregnancies in Relation to Chorionicity at a Tertiary Care Centre in Central Kerala, India: A Prospective Cohort Study - P Hridya; AV Deepak; RP Reena (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: In recent years, there has been a significant increase in the incidence of multiple births due to advanced maternal age at conception and the growing use of infertility treatment. Multiple pregnancies are associated with both maternal and perinatal complications. Maternal complications include anaemia, gestational hypertension, gestational diabetes, preterm labour, operative delivery and postpartum haemorrhage. Preterm birth, growth discordance and complications specific to monochorionic twins predispose these babies to adverse perinatal outcomes. Aim: To assess the perinatal outcomes of twin pregnancies and compare the outcomes of monochorionic and dichorionic pregnancies. Materials and Methods: The present prospective cohort study was conducted in the Department of Obstetrics and Gynaecology, Government Medical College (Tertiary care centre), Thrissur, Kerala, India, from September 2019 to August 2020. All twins who delivered at a gestational age of ≥28 weeks during the study period were recruited, totaling 76 twin pregnancies. A structured proforma was used to collect demographic and clinical details, including mode of conception, chorionicity, maternal complications, intrapartum events and neonatal outcomes. Data were analysed using Epi Info software. Results: The mean maternal age of the study participants was 28.39±6.29 years. The incidence of twin pregnancies delivering at ≥28 weeks at Government Medical College, Thrissur, during the study period was 2.8% (76 twins out of 2709 deliveries). Infertility treatment (ovulation induction alone or Assisted Reproductive Techniques (ART) was associated with dichorionic twinning in 19.7% (15 out of 76 twin pregnancies), with a p-value of 0.008. Maternal complications were similar in both dichorionic and monochorionic twins. Preterm Premature Rupture of Membranes (PPROM) occurred in 23 (28.75%) twin pregnancies, 19 (23.75%) had Gestational Diabetes Mellitus while 13 (16.25%) participants had anaemia. Foetal growth restriction, congenital anomalies, and discordant growth were more prevalent in monochorionic twin pregnancies compared to dichorionic twin pregnancies. Although the proportion of babies requiring Neonatal Intensive Care Unit (NICU) admission was higher in monochorionic twins (64% vs 53.9%), the proportion of neonatal deaths was nearly equal between monochorionic and dichorionic twins (10% vs 9.8%). Conclusion: In the present study, there was no statistical difference in maternal complications between monochorionic and dichorionic twins. However, monochorionic pregnancies had a poorer perinatal outcome compared to dichorionic pregnancies.